Peran Kepercayaan Konsumen sebagai Mediasi Ulasan Online dan Rating Produk terhadap Keputusan Pembelian E-Commerce Generasi Z - Tiana Fika Sari; Nurul Kholifah (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study analyzes the effect of online reviews and product ratings on purchase decisions with consumer trust as a mediating variable among Generation Z e-commerce consumers. The increasing use of e-commerce has made electronic word of mouth an important information source in reducing purchase uncertainty. This research applies a quantitative explanatory approach using data collected from 100 Generation Z respondents through an online questionnaire. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that online reviews have a significant effect on consumer trust and purchase decisions, both directly and indirectly through consumer trust. Product ratings significantly affect consumer trust but do not influence purchase decisions directly or indirectly. Consumer trust has a positive and significant effect on purchase decisions. These findings indicate that narrative and experience-based information is more influential than numerical ratings in shaping Generation Z’s purchasing decisions. The study implies that e-commerce platforms should focus on managing credible and informative online reviews to strengthen consumer trust.